Keanekaragaman Tanaman Sayur Lokal Pekarangan dan Potensinya sebagai Sumber Nutrisi - Pramesti, Dias Idha (Biocaster : Jurnal Kajian Biologi, 2024)
Yards have a role in maintaining community food security with one of the food sources being local vegetables. This group of plants has advantages, including having adapted to the local environment, being easy to obtain, and containing substances that are beneficial to the body. This research aims to determine the diversity and nutritional potential of local garden vegetables in Bantul Regency. Data collection was carried out using survey methods and semi-structured interviews using questionnaire instruments. The location for data collection was determined purposively, covering areas in 7 sub-districts (kepanewon) in Bantul Regency. Plant samples are then documented and identified. Proximate, mineral and vitamin analyzes were carried out on kedi (Cnidoscolus chayamansa McVaugh), tayuman (Bauhinia purpurea L.), and mulberry (Morus sp.) plants. The research results showed that there were 71 species from 27 families of local vegetables in residents’ yards. The types of local vegetable plants recorded are in the Fabaceae family. Meanwhile, the plants that are often found in residents’ yards are chilies (Capsicum spp.), bananas (Musa paradisiaca L.), eggplant (Solanum melongena L.), cassava (Manihot utilissima Pohl.), spinach (Amaranthus sp.), and jackfruit ( Artocarpus heterophyllus Lam.). Comparison of the results of nutritional analysis of three vegetables shows that among the three plants in 100 grams of sample there is the highest value of sodium in kedi leaves, namely 22.73 mg; protein content 7.36%, vitamin A 209.88 mg, and potassium 441.78 mg in tayuman; and energy from total fat 24.57 Kcal, total energy 84.85 Kcal, and calcium 485.43 mg in mulberries.